ANALYSIS OF THE ABILITY OF NANO ETHANOL EXTRACT OF CORIANDER (Coriandrum sativum L.) SEEDS TO REDUCE BLOOD GLUCOSE LEVELS IN HYPERGLYCEMIC WISTAR RATS - Wahjuni, Sri; Parwata, I M.O. Adi; Putra, A.A. Bawa; Lahaya, Mustika (Jurnal Ilmu Pendidikan Indonesia, 2023)
Nano ethanol extract of coriander seeds is proven to increase the activity of active compounds in the body. This research was conducted to see the ability of coriander seed ethanol extract to reduce glucose levels in hyperglycemic rats compared to coriander seed extract without nano. The size of the nano coriander seed extract after being characterized by the Particle Size Analyzer (PSA) was 182.4 nm and the zeta potential value was -1.5 mV. The activity test results showed the ability of the coriander seed ethanol extract to be more effective in lowering blood glucose levels compared to the coriander seed extract without nano. Identification of compounds thought to be effective as hypoglycemics using Liquid Chromatography-Mass Spectrometry/Mass Spectrometry (LC-MS/MS), identified 7 compounds namely phenylalanine, indole, apigenin, 4-methoxybenzaldehyde, 2,5-dimethoxybenzaldehyde, 2-flouren-9-ylidenemethyl-pyridine , and 5-pentyl-1,3-benzenediol, which are suspected to be active as hypoglycemics are phenylalanine, indole, apigenin, and 2,5-dimethoxybenzaldehyde. The ethanol extract of coriander seeds in nanoparticle preparations is more effective in reducing blood glucose levels than the ethanol extract of coriander seeds without nano preparations